Outcomes and cost of major liver resection using combined ligasure and stapler: a propensity score matching study - Abbasi Dezfouli, Sepehr; Dooghaie Moghadam, Arash; Sabetkish, Nastaran; Khajeh, Elias; Ramouz, Ali; Majlesara, Ali; Mieth, Markus; Chang, De-Hua; Golriz, Mohammad; Mehrabi, Arianeb (Journal of Clinical Medicine, 2025)
Background: Bile leakage remains a significant challenge following major liver resection, with potential for improvement depending on the transection technique used. In this study, we aimed to evaluate the effectiveness of our hybrid resection technique—utilizing both LigaSure and stapler devices—in reducing bile leakage after major liver resection compared to our conventional stapler-only technique. As a secondary aim, we compared overall morbidity, costs, and reimbursements. Method: Patients who underwent major hepatectomy without biliary reconstruction using either the hybrid or stapler technique between August 2014 and December 2021 were included in the study. Propensity score matching was performed using a one-to-two algorithm. Perioperative data, bile leakage rates, and cost and reimbursement information based on the diagnosis-related group (DRG) system were analyzed. Results: In total, data from 492 patients were evaluated (hybrid = 152; stapler = 340). After one-to-two propensity score matching, the operation time was significantly longer in the hybrid group (p = 0.005). A cost analysis showed no significant difference in total operative costs between the two techniques (p = 0.092). However, the hybrid group had a significantly lower rate of bile leakage (p = 0.002), as well as shorter intensive care unit (ICU) and overall hospital stays (p = 0.034 and p = 0.007, respectively). Consequently, ICU and ward costs were significantly lower in the hybrid group (p = 0.024 and p = 0.014, respectively) compared to the stapler group. The financial difference calculated as DRG reimbursement minus costs was two-fold higher in the hybrid group (p = 0.02). Conclusions: Although the hybrid technique resulted in a longer operating time, it proved superior to the stapler technique in reducing postoperative bile leakage and shortening ICU and hospital stays. Furthermore, the use of the hybrid technique was more cost efficient and resulted in a greater positive financial margin.
Gesehen am 17.10.2025